Pidgins and Creoles: Birth of Languages (Jurnal Adabiya, 2020)
This article presents an outlook of pidgins and creoles starting from the background of the ariseof the using of pidgins and creoles in the world. To have a clear understanding of what pidgins and creolesare the definition of both terms are explained briefly here. This article also discusses some distinctions ordistinctive features of pidgins and creoles and the community using pidgins and creoles in the world. Atthe end of the discussion, this article describes some brief discussions related to some reasons stating thatpidgins and creoles are born as languages.